EGFR family and Src family kinase interactions: mechanics matters?. (April 2018) - Chen, Zhongwen; Oh, Dongmyung; Dubey, Alok Kumar; Yao, Mingxi; Yang, Beverly; Groves, Jay T; Sheetz, Michael
Abstract : Receptor tyrosine kinases (RTKs), such as the EGF receptor family, and adhesion molecules, such as integrins, have historically been viewed to have distinctly separable roles in the cell. In this classical view, integrins mediate mechanical interactions between the cell and its surrounding extracellular matrix while RTKs handle signaling to modulate cellular behavior. Although crosstalk between these receptor pathways has been known to exist for a long time, this has generally been attributed to effects significantly downstream from the receptors themselves. In recent years, however, EGFR family RTKs have been found to directly participate in integrin-mediated force sensing, revealing a more complex interplay among these cellular components than originally appreciated. Here we briefly review the classical understanding of EGFR family RTK signaling and then provide a broadened perspective based on recent results.